2015
DOI: 10.1259/bjr.20150593
|View full text |Cite
|
Sign up to set email alerts
|

Effects on short-term quality of life of vacuum-assisted breast biopsy: comparison between digital breast tomosynthesis and digital mammography

Abstract: Effects on short-term quality of life of vacuum-assisted breast biopsy: comparison between digital breast tomosynthesis and digital mammography. Br J Radiol 2015; 88: 20150593. FULL PAPEREffects on short-term quality of life of vacuum-assisted breast biopsy: comparison between digital breast tomosynthesis and digital mammography 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
3
1
Order By: Relevance
“…In our study, we did not find a significant association between TMI scores and age, previous personal history or family history of breast cancer, and, in particular, we found no relationship between age and 'pain or discomfort during the test'. Our results differ from a previous study in which Tagliafico et al [10] found that age was a significant predictor of short-term quality of life related to breast biopsy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, we did not find a significant association between TMI scores and age, previous personal history or family history of breast cancer, and, in particular, we found no relationship between age and 'pain or discomfort during the test'. Our results differ from a previous study in which Tagliafico et al [10] found that age was a significant predictor of short-term quality of life related to breast biopsy.…”
Section: Discussioncontrasting
confidence: 99%
“…The first seven attributes (a-g) were directly related to the examination, while the remaining two (h and i) were only indirectly related (or not necessarily related) to the examination, as already hypothesised by Tagliafico et al [10] for the attribute (h).…”
Section: Data Collectionsupporting
confidence: 55%
See 1 more Smart Citation
“…As just stated, no B1 results were found at histology; thus, no procedure had to be repeated. This finding is actually a crucial strength of this technique because it has been demonstrated that VAB biopsies are linked to a decrease in the short-term quality of life (QoL) of women (21,22).…”
Section: Discussionmentioning
confidence: 95%
“…VABBs were performed by 3 radiologists with 15, 12, and 11 years of experience in breast imaging field. The procedure was performed with a DBT-guided stereotaxic VABB system (Selenia Dimensions system's Genius TM 3D Mammography TM ; Hologic, Bedford, MA, USA), with the patient being in a sitting position although less comfortable than the supine position [ 16 ]. The entry approach was chosen to ensure the shortest possible distance between the skin and the target lesion.…”
Section: Methodsmentioning
confidence: 99%